2021
DOI: 10.1128/msphere.00982-20
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Ecological Resistance of the Gut Microbiota in Response to Clindamycin Challenge in Mice Colonized with the Fungus Candida albicans

Abstract: The mammalian gut microbiota is a complex community of microorganisms which typically exhibits remarkable stability. As the gut microbiota has been shown to affect many aspects of host health, the molecular keys to developing and maintaining a “healthy” gut microbiota are highly sought after. Yet, the qualities that define a microbiota as healthy remain elusive. We used the ability to resist change in response to antibiotic disruption, a quality we refer to as ecological resistance, as a metric for the health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…It is suggested that the strictly anaerobic bacterial populations which predominate in the gut in CL-treated rats ( Enterobacteriaceae) are responsible for the inhibition of C. albicans adhesion, colonization, and diffusion from the intestinal tract ( Table 3 ; Groups 2, 3, and 4). This explanation could be further supported through considering the most recent work of Markey et al [ 64 ], who reported that bacterial colonization and the C. albicans are more easily changed by CL treatment providing perception into the microbiota response to acute CL challenge and the effect of C. albicans colonization on ecological resistance.…”
Section: Resultsmentioning
confidence: 85%
“…It is suggested that the strictly anaerobic bacterial populations which predominate in the gut in CL-treated rats ( Enterobacteriaceae) are responsible for the inhibition of C. albicans adhesion, colonization, and diffusion from the intestinal tract ( Table 3 ; Groups 2, 3, and 4). This explanation could be further supported through considering the most recent work of Markey et al [ 64 ], who reported that bacterial colonization and the C. albicans are more easily changed by CL treatment providing perception into the microbiota response to acute CL challenge and the effect of C. albicans colonization on ecological resistance.…”
Section: Resultsmentioning
confidence: 85%
“… 20 , 21 The fungus also has a role in the ability of intestinal microbial consortia to resist change in response to antibiotic disruption, which is termed ecological resistance. 22 Furthermore, gut fungal dysbiosis has been associated with reduced efficacy in fecal transplants currently in use to treat recurrent Clostridium difficile infections. 23 …”
Section: Interdependencies Between Bacteria and Fungi In The Mammalian Gutmentioning
confidence: 99%
“…20,21 The fungus also has a role in the ability of intestinal microbial consortia to resist change in response to antibiotic disruption, which is termed ecological resistance. 22 Furthermore, gut fungal dysbiosis has been associated with reduced efficacy in fecal transplants currently in use to treat recurrent Clostridium difficile infections. 23 In a longitudinal study of a cohort of 178 preterm infants in which the assembly of the intestinal microbiota was monitored, Rao et al 24 were able to infer several interdependencies between specific fungi and bacterial taxa.…”
Section: Changes In Gut Fungal Communities Lead To Bacterial Dysbiosismentioning
confidence: 99%